(untitled) (Research, Society and Development, 2023)
Objective: To evaluate the series of patients undergoing surgical correction of iatrogenic lesions of the bile ducts at the General Surgery Service of Fundação Santa Casa de Misericórdia do Pará (FSCMPA). Data analysis: A retrospective descriptive observational study will be carried out by collecting data from medical records of patients undergoing conventional or laparoscopic cholecystectomy, referred to the FSCMPA, which will be analyzed through expository tables using. Result: 67 biliodigestive derivations were performed, between 2016 and 2022, 17 (25.4%) were due to iatrogenic injuries of the biliary tract, with no deaths recorded between them. Most (14 or 82.4%) were female. 47.1% of the individuals were between 20 and 39 years old. Most patients (12 or 70.6%) did not use blood products, all 17 patients (100%) required postoperative care in an intensive care unit. Final considerations: The data show that the female public was the most affected by injuries, all of them required postoperative care in the ICU. With regard to treatment, in all cases, hepatojejunoanastomosis-type biliodigestive bypass was performed.